Morbidity and mortality from birth before arrival at Siriraj Hospital - Korakot Sirimai (2018)
Objective: To identify maternal and infant morbidity and mortality from birth before arrival at Siriraj Hospital. Study design: Prospective case-control study. Setting: Department of Obstetrics & Gynecology, Faculty of Medicine Siriraj Hospital, Mahidol University. Subjects: Three hundred and twenty patients, who had delivered at Siriraj Hospital, were divided into two groups. The study group consisted of 160 patients, who gave birth before admission to the labour room of Siriraj Hospital. The control group consisted of 160 patients, who had normal deliveries in the labour room of Siriraj Hospital at the same period of time. Intervention: Interviewing the patients and reviewing the medical records of the mothers and infants from both groups. The data were analyzed by using the EpiInfo program. Main outcome measure: Maternal and infant characteristics after delivery, maternal and infant outcomes including puerperal morbidity, low birth weight, perinatal death and infant morbidity. Results: The study showed that the mothers in the study group had to stay in the hospital longer than the control group (3.9 ± 2.5 days and 3.6 ± 1.3 days respectively, p < 0.05). The infants in the study group also had to stay in the hospital longer than the control group (5.1. ± 6.5 days and 3.3 ± 1.7 days respectively, p < 0.001). The birth weights of infants in the study group were significantly lower than in the control group (2753.4 ± 594.1 grams and 3016.6 ± 405.0. grams respectively, p < 0.001). The body temperature of the newborns in the study group were also lower than in the control group (36.2 ± 0.6 degree Celsius and 37.0 ± 0.4 degree Celsius respectively, p < 0.05). Concerning maternal and infant outcomes, all variables including low birth weight, perinatal death and infant morbidity were better in the control group significantly (p < 0.05) except for puerperal morbidity that had no significant difference (p = 0.77). Conclusion: From the present study, the authors confirmed the higher mortality and morbidity rate of infants who were born unexpectedly before hospital admission. However, there was no difference in morbidity between the mothers of both groups.